Thrombin Generation Kinetics are Predictive of Rapid Transfusion in Trauma Patients Meeting Critical Administration Threshold. Issue 3 (March 2021) - MacArthur, Taleen A.; Spears, Grant M.; Kozar, Rosemary A.; Dong, Jing-fei; Auton, Matthew; Jenkins, Donald H.; Bailey, Kent R.; Ashrani, Aneel A.; Ferrara, Mike J.; Immermann, Joseph M.; Halling, Timothy M.; Park, Myung S.
ABSTRACT: Introduction: We hypothesize that a patient (pt) with accelerated thrombin generation, time to peak height (ttPeak), will have a greater odds of meeting critical administration threshold (CAT) criteria (> 3 packed red blood cell [pRBC] transfusions [Tx] per 60 min interval), within the first 24 h after injury, independent of international normalized ratio (INR). Methods: In a prospective cohort study, trauma patients were enrolled over a 4.5-year period and serial blood samples collected at various time points. We retrospectively stratified pts into three categories: CAT+, CAT− but receiving some pRBC Tx, receiving no Tx within the first 24 h. Blood collected prior to Tx was analyzed for thrombin generation parameters and prothrombin time (PT)/INR. Results: A total of 484 trauma pts were analyzed: injury severity score = 13 [7, 22], age = 48 [28, 64] years, and 73% male. Fifty pts met criteria for CAT+, 64 pts CAT−, and 370 received no Tx. Risk factors for meeting CAT+: decreased arrival systolic blood pressure (OR 2.82 [2.17, 3.67]), increased INR (OR 2.09, [1.66, 2.62]) and decreased time to peak OR 2.27 [1.74, 2.95]). These variables remained independently associated with increased risk of requiring Tx in a multivariable logistic model, after adjusting for sex and trauma type. Conclusions: Pts in hemorrhagic shock, who meet CAT+ criteria, are characterized by accelerated thrombin generation. In our multivariable analysis, both ttPeak and PT/INR have a complementary role in predicting those injured patients who will require a high rate of Tx. Abstract : Supplemental Digital Content is available in the text